Impacts of Online Child Sexual Abuse in the Gambia: The Perspective of Child Protection Officers (Case Study: Serekunda Tourism Development Areas) - Yahya Muhammed Bah (Britain International for Academic Research (BIAR-Publisher), 2026)
The digital technology has positively transformed the life and living conditions of many people around the globe. However, studies have revealed some negative socio-economic, political, cultural; and environmental impacts. This case study was conducted to interrogate online child sexual abuse and exploitation in The Gambia focusing on the motivating factors, techniques, negative impacts, victims and perpetrators support services, preventive strategies; and institutional collaboration. Based on the findings the negative consequences encompass: psychological trauma, poor academic performance, mental disorders, drug abuse, diseases, stigma and discrimination, difficulties in the upbringing of children; and sanctions to the travel and hospitality industry.